Social learning of acoustic anti-predator cues occurs between wild bird species - Keen, SC; Cole. EF; Sheehan, MJ; Sheldon, BC (The Royal Society, 2020)
In many species, individuals gather information about their environment both through direct experience and through information obtained from others. Social learning, or the acquisition of information from others, can occur both within and between species and may facilitate the rapid spread of antipredator behaviour. Within birds, acoustic signals are frequently used to alert others to the presence of predators, and individuals can quickly learn to associate novel acoustic cues with predation risk. However, few studies have addressed whether such learning occurs only though direct experience or whether it has a social component, nor whether such learning can occur between species. We investigate these questions in two sympatric species of Parids: blue tits (Cyanistes caeruleus) and great tits (Parus major). Using playbacks of unfamiliar bird vocalizations paired with a predator model in a controlled aviary setting, we find that blue tits can learn to associate a novel sound with predation risk via direct experience, and that antipredator response to the sound can be socially transmitted to heterospecific observers, despite lack of first-hand experience. Our results suggest that social learning of acoustic cues can occur between species. Such interspecific social information transmission may help to mediate the formation of mixed-species aggregations.